The concept of “child” in the Latvian models of education - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are This article presents the results of the study of the concept of “child” in the Latvian model of education. A study of the concept of “child” is associated with the study of culturally - conditional model of raising children, having a single structure, but different Model of education - a method of transmitting culture, in the broadest sense from one generation to the next, holds both universal and culturally -conditional features. Type of culture (individual or collective, open or closed, simple or complex), the inclusion of the child in life of the adult, the values of the people and their hierarchy, as well as an idea of how adults want to see the child when he grows up, defines the methods of education, as well as their evaluation of the culture-carriers themselves.Vast material for the study of the concept of "child" is provided by the folk lullabies and folk songs, Latvian sayings, as well as the modern parents’ idea of a child.